Updating of lesion definitions and validation of MRI spinal lesions in patients with axial spondyloarthritis, conducted by the ASAS MRI working group - Shandor F. Erdes; Alexander V. Smirnov (Научно-практическая ревматология, 2024)
The article presents an updated version of the definitions of spinal lesions that are observed in patients with axial spondyloarthritis on MRI. It was developed by a special working group ASAS. The aim of the work is to unify the definitions and concepts used in the description of spinal MRI in patients with chronic back pain to improve the diagnosis of axial spondyloarthritis.